Philippine multilingual medical thesaurus on anatomy: sense organs and diseases female urogenital and pregnancy complications in Iluko - Calipjo, Ken Mervin, T. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
The practice of medicine has been improving in the last 20 years with the discoveries in the biological sciences and advances in information technology. With the continued progress in the field of medicine the communication barrier between the medical professionals and patients due to differences in medical knowledge also continues to widen. In the local setting, the diversity of Philippine language brings complications in terms of communication between medical professionals and patients. To address this problem, the Philippine Multilingual Thesaurus project was conceived.